The Construction Development Map of Magelang City - Indah Khalimatul Lestari; Rian Destiningsih (Universitas Gorontalo, 2021)
The existence of construction in an area will have an influence on regional development. Likewise in the City of Magelang, the construction sector is a sector that contributes a fairly large GRDP with the construction of construction such as buildings and roads as the provision of facilities and infrastructure will result in an increase in community welfare which will also affect economic growth. The purpose of this study was identif construction sector in the form of roads and buildings with the results of a map of the distribution of construction in the City of Magelang by looking at the local construction service company so that it can be a reference in improving regional development, especially the construction sector to realize adequate infrastructure. As well as the socio-economic benefits of having a construction service company in Magelang City. This study used qualitative descriptive method with questionnaire, interview, observation and observation techniques. In the 2020 construction distribution map, there are high, medium and low building densities where high building densities dominate in the middle of the city along the main road. Road construction helps the distribution of goods and services and maximizes community access. The existence of a local construction service company provides benefits to the community both socially and economically, such as employment, services, and improvement of infrastructure facilities for the community. However, stronger synergy is needed to realize quality construction and utilize local resources in its implementation.